Health care costs of comorbidities in patients with HIV infection in Italy. An estimate using a Delphi panel - Lucioni, Carlo; Mazzi, Silvio; Bensi, Giuliano (Farmeconomia. Health Economics and Therapeutic Pathways, 2006)
In HIV affected patients, co-morbidities (also termed opportunistic infections or AIDS-defining events) characterise the disease progression, resulting from deteriorating immunologic status. They are the commonest cause of morbidity and mortality among such patients and may account for a major share of the overall health cost of HIV. Given the paucity of published data about co-morbidities costs in Italy, an estimation was targeted and then reached using a Delphi panel. A questionnaire, the same for each of the 22 co-morbidities considered, was designed where type and quantity of resources used (which and how many lab tests, hospital admissions, drugs) were to be reported concerning three steps (diagnosis, acute treatment, follow-up within one year) in each comorbidity. Six experts, belonging to as many infectious diseases centres located all over Italy, were involved to independently complete the questionnaires. Information about resources in physical terms, collected from the first round of the panel, was converted into monetary terms, aggregated (a cost for each co-morbidity was estimated averaging the corresponding six costs deriving from the centres), and sent back to the experts. Each expert received also the costs per co-morbidity data as resulting from the others’ answers (though in anonymous form) and was invited to confirm or revise the answers he had previously given. The same processing was then performed when information was available from the second round. A substantial convergence among the final data from the different experts came into evidence. According to this Delphi panel results, the overall average cost for a HIV co-morbidity in Italy is 8,967 euros; the most expensive co-morbidity is CMV retinitis (27,946 euros) and the cheapest is herpes simplex (2,057 euros).